FAQ: Initial questions about thesis supervision in Law - Desmond Manderson (Legal Education Review, 1997)
The initials — LLM or DCL or PhD — don’t mean much. But the experience of writing that thesis was one of the most important of my life: adventurous, delicious, painful. It changed me as a writer and a person in ways I cannot begin to catalogue. It gave me the time, and the space, to think and to read, and perhaps even to grow up (a little)...The importance of the experience and the privilege of the position comes about because writing a thesis is a licence to ask questions: questioning what the field of law is and offers, questioning how things have been approached and how they might be changed, questioning one’s own thinking, assumptions, and expectations.